Perception of Stakeholders for Meat Qualities among Value Chain Actors in Ethiopia - Birmaduma Gadisa Muleta (Veterinary Medicine International)
Perception is the knowledge of an individual/group gained from experience and impressions of the ideal situation. Ethiopian livestock marketing has a different stage and large actors. However, in the flow chain, there is less communication. Because they only perceive for their benefit rather than care for a quality product. This happened because the production mapping was not understood among them. The majority of producers fetch too old animals after being culled from production and those that might be abnormal due to disease and chronic stress. Traders transport mixed animals through nondedicated vehicles and long trekking without feeding and watering. Abattoir men worked with poor facilities. They perceived that the time stay animals in Lairage, breeding, bleeding, and carcass handling is the major problem in meat quality in Ethiopia. The slaughtering has been conducted in brutal ways of stunning using either a hammer or knife at the atlanto-occipital space of the animal on the floor side by side. The majority of butchers in Ethiopia are located on the main road for their products to be easily displayed to clients, and they hang meat on the open shelf without packing, which exposes the product to aerobic spoilage by bacteria and yeasts. Traders/brokers are promoting the product based on the commission they earn rather than the quality and health of the animals. However, as a principle, each actor has a responsibility to manage risk as they benefit socially and economically from firms. Government entities should play an important role in shaping actors’ perceptions and understanding of biosecurity measures. Mainly, the interventions should focus on improving business models and technological adoption. This model is used for improving vertical relationships among operational actors, horizontal relationships with logistics providers, and market promotion measures to attract foreign direct investors and importers, transforming traditional practices of animal husbandry into commercial ones. Because a key activity for each value chain actor is availing of the final product safely at the right place and time. The review was designed to convey information to enhance the linkage between meat value chain actors and optimize management skills in Ethiopia.